2012
DOI: 10.1177/0956797612452572
|View full text |Cite|
|
Sign up to set email alerts
|

Can Emotion Regulation Change Political Attitudes in Intractable Conflicts? From the Laboratory to the Field

Abstract: We hypothesized that an adaptive form of emotion regulation-cognitive reappraisal-would decrease negative emotion and increase support for conflict-resolution policies. In Study 1, Israeli participants were invited to a laboratory session in which they were randomly assigned to either a cognitive-reappraisal condition or a control condition; they were then presented with anger-inducing information related to the Israeli-Palestinian conflict. Participants in the reappraisal condition were more supportive of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
200
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 24 publications
3
200
1
2
Order By: Relevance
“…A successful unfreezing process should increase the individual's openness to previously contradictory views regarding the conflict, the adversary, and the in-group (5). With this challenge, a growing body of research has attempted to identify methods of intervention that can unfreeze deeply rooted conflict-supporting narratives among groups in conflict (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A successful unfreezing process should increase the individual's openness to previously contradictory views regarding the conflict, the adversary, and the in-group (5). With this challenge, a growing body of research has attempted to identify methods of intervention that can unfreeze deeply rooted conflict-supporting narratives among groups in conflict (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Finally, our findings might also carry implications for the study of intergroup relations, more generally. Previous research has shown that the experience of negative emotions leads to more support of aggressive actions towards the adversarial group (Cheung-Blunden & Blunden, 2008;Halperin et al, 2013;Skitka et al, 2006). The current investigation suggests that such emotional experiences may be driven by a desire to strengthen group coherence.…”
Section: Theoretical Implicationsmentioning
confidence: 56%
“…Importantly, people can regulate their emotions in both individual (e.g., Gross, 2007;Gross, Richards, & John, 2006) and in group contexts (e.g., Halperin, Pliskin, Saguy, Liberman, & Gross, 2014;Halperin, Porat, Tamir, & Gross, 2013).…”
Section: The Instrumental Approach To Emotion Regulationmentioning
confidence: 99%
“…This is encouraging in terms of the applied interventions of these results, even though future studies are needed to shed light on such a field. In this vein, some authors have also shown that an emotion regulation strategy that is strongly related to happiness (i.e., cognitive reappraisal; Gross and John 2003) can represent a helpful resource to cope with relevant social issues such as climate change and intractable conflicts (e.g., Israeli-Palestinian conflict; Gross et al 2013;Halperin et al 2013;Halperin 2014;Panno et al 2015). Future studies could test whether well-established interventions aimed at the enhancement of such an emotion regulation strategy might also be effective in coping with the immigration issues (see Halperin et al 2013;Halperin 2014; for more details).…”
Section: Discussionmentioning
confidence: 99%